Multicentric non-enhancing lesions in glioblastoma: A retrospective study. (March 2021) - Benouaich-Amiel, Alexandra; Khasminsky, Vadim; Gal, Omer; Weiss, Tamara; Fichman, Susana; Kanner, Andrew A.; Berkowitz, Shani; Laviv, Yosef; Mandel, Jacob; Dudnik, Elizabeth; Siegal, Tali; Yust-Katz, Shlomit
Highlights: Multiple non enhancing lesions are not uncommon in newly diagnosed glioblastoma. Non-enhancing lesions may display aggressive behavior with high risk of progression. Radiotherapy field should be discussed carefully for those patients. Abstract: Glioblastoma (GBM) typically presents as a single lesion. Multicentric GBM are defined as well separated lesions on MRI (enhancing and non-enhancing). Multicentric GBM with non-enhancing lesions (MNE-GBM) are rarely described in literature. We aimed at describing the radiologic characteristics, treatment, and clinical course of those patients. The institutional neuropathological database was searched for GBM patients diagnosed between 1/1/2015 and 31/05/2018. All pre-operative MRI brain scans were reviewed to identify patients with MNE-GBM. Electronic medical records and follow-up MRI scans were reviewed to assess progression-free survival (PFS) and overall survival (OS). Out of 149 adult patients with newly diagnosed GBM, 12 met the inclusion criteria of MNE-GBM, all of them presented at least one enhancing lesion. Median follow-up for the MNE-GBM patients was 16.1 months. At last follow-up, all patients had recurrence (median PFS 7.6 months) and eleven patients had deceased. Median OS was 16.2 months (95% CI, 4.1–27.5). Eleven patients received radiotherapy concomitant with temozolomide as initial treatment. Radiation field included all the disease foci (enhancing and non-enhancing lesions) in 8 patients, five of them progressed within the non-enhancing lesion. Three patients did not receive radiation for the entire non-enhancing lesions, and two of them progressed within the non-irradiated areas. In conclusion, MNE-GBM is not rare, and has high risk of aggressive progression within the separate non-enhancing lesion.